Artificial intelligence for IoT cookbook : over 70 recipes for building AI solutions for smart homes, industrial IoT, and smart cities /: over 70 recipes for building AI solutions for smart homes, industrial IoT, and smart cities. (2020) - Roshak, Michael
No abstract available